Addressing COVID-19 impacts on agriculture, food security, and livelihoods in India - Dev, S. Mahendra (International Food Policy Research Institute, 2020)
India has taken early action to limit the spread of COVID-19, ordering a 21-day nationwide lockdown for its population of 1.3 billion people starting March 25. Subsequently the lockdown was renewed three more times before May 31. The unlocking of India began June 1, except in containment zones. The novel coronavirus has spread widely in India and the number of reported infections is 217,000, with relatively few deaths, at 6,075, as of June 4. However, as COVID-19 cases are increasing fast, there is great concern about the disease’s potential spread and impact. India has to be ready for a possible surge. The government views the pattern of the spread of COVID-19 as similar to the 2009 H1N1 influenza pandemic, meaning the spread is unlikely to be uniform. It is concentrated in a few big cities and states and its spread is less in rural areas and smaller towns and cities.